Induction as a research area of pedagogical interest : the first year of work and induction into a job as field of interest for pedagogical research? - Geiben, Marthe [Verfasser] (My University, 2012)
"In this article, the author presents key questions on induction into work and the first year of employment of job entrants with midlevel qualifications. To point out the most relevant issues in research and practice, the author will in a first step define the used understanding of the key concepts: induction, job entrants and midlevel qualification. In a second step, she will show some of the relevant disciplines already dealing with the issue of the first year of work, e.g. human resources development, pedagogic, or sociology. In a third step, current research projects will be outlined and in the conclusion, open (research) questions on this special period in (professional) life will be stressed." (Autorenreferat, BIBB-Doku)
Keywords: G 1.3.2.2.3 Zweite Schwelle, in Arbeit; Berufseinmündung; Zweite Schwelle; Berufsanfänger; Mittlere Qualifikation; Einarbeitung; Personalentwicklung